The Fracture Resistance of Endodontically Treated Maxillary Premolars Restored with Direct Composite Onlay Using Different Resin Composite - Angwarawong, Thidarat; Keatdumrong, Patchareeporn; Thitthaweerat, Suppason; Angwaravong, Onauma (Khon Kaen University Dental Journal, 2020)
The purpose of this study is to evaluate fracture resistance and fracture pattern of endodontically treated upper first premolars that were restored with direct onlay technique using different resin composite materials. Seventy upper first premolars were divided into seven groups (n=10). The first ten premolars were left intact (INT) as the negative control group, while the remaining premolars received class II MOD cavity preparation and conventional root canal treatment. The positive control group was restored with interim restoration (IRM), whereas the experimental groups were prepared for direct composite onlay and were then restored with Filtek™ Z250 (Z250), or Filtek™ Bulk Fill Posterior (FBF), or SonicFill™ 2 (SBF), or EverX Posterior plus Filtek™ Z250 (EXP) or Build-It™ FR plus Filtek™ Z250 (BFR), as designed. All specimens were stored in 100% humidity at 37ºC for 24 hours before the fracture test. Each specimen was mounted and aligned at 45-degree angle to the horizontal plane. Measurement of fracture resistance was done with the universal testing machine at a crosshead speed of 0.5 mm/sec using a 3 mm diameter metal ball pressing at palatal incline plane of buccal cusp. The maximum force at the fracture (mean±SD) was 654.47±105.32 N, 314.20±93.82 N, 583.61±135.04 N, 541.84±144.87 N, 598.62±136.45 N, 600.65±166.69 N and 587.37±91.09 N for INT, IRM, Z250, FBF, SBF, EXP and BFR, respectively. One-way ANOVA with Tukey’s HSD test showed no significant difference in the mean maximum force at fracture among the intact teeth group and all direct composite onlay groups (p>0.05). The IRM group had the lowest fracture resistance value, which differed statistically from the other groups ((p<0.05). More than 70% of fractures in group INT, IRM, Z250, and SBF were restorable while only half of group FBF, EXP and BFR were considered restorable. Conclusion could be drawn that direct composite onlay restorations of endodontically treated upper first premolar with different materials had comparable fracture resistance.